1999
DOI: 10.1002/(sici)1096-8628(19991119)87:2<139::aid-ajmg5>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Rare interstitial deletion (2)(p11.2p13) in a child with pericentric inversion (2)(p11.2q13) of paternal origin

Abstract: An unbalanced 46,XY,der(2)del(2)(p11.2p13) inv(2)(p11.2q13) karyotype was found in a phenotypically abnormal child with a de novo interstitial deletion of band 2p12 associated with an inv(2)(p11.2q13) inherited from the father. The inv(2) is generally considered a benign familial variant without significant reproductive consequences. However, our findings led us to consider a previously proposed mechanism of unequal meiotic crossing over at the base of a parental inversion loop, which could lead to either a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We have listed the clinical manifestations of the six previously published patients with deletions in 2p11.2–p12 and of our patient in Table I [Prasher et al, 1993; Los et al, 1994; Wenger and McPherson, 1997; Lacbawan et al, 1999; Barber et al, 2005]. Apart from developmental delay/mental retardation, there were no other consistent findings which would allow the delineation of a clinically recognizable 2p11.2–p12 deletion syndrome.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have listed the clinical manifestations of the six previously published patients with deletions in 2p11.2–p12 and of our patient in Table I [Prasher et al, 1993; Los et al, 1994; Wenger and McPherson, 1997; Lacbawan et al, 1999; Barber et al, 2005]. Apart from developmental delay/mental retardation, there were no other consistent findings which would allow the delineation of a clinically recognizable 2p11.2–p12 deletion syndrome.…”
Section: Discussionmentioning
confidence: 83%
“…Interstitial deletions of chromosome bands 2p11.2–p12 are rare, and only six patients have been reported to date [Prasher et al, 1993; Los et al, 1994; Wenger and McPherson, 1997; Lacbawan et al, 1999; Barber et al, 2005]. These patients had developmental delay/mental retardation and variable additional problems such as hypospadias, facial dysmorphisms, club foot or Wilms tumor (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…Unbalanced recombinant products involving an inv(2)(p11.2q13) are very rare and have involved crossing-over adjacent to, rather than within, the inverted segment. 18,19 Typing of microsatellites outside the inverted segment showed that recombination suppression appeared to extend for variable distances beyond the breakpoints (table 5). Two of the group C families shared the same haplotype well beyond the inversion breakpoints, particularly on proximal 2p.…”
mentioning
confidence: 99%
“…The same chromosomal anomaly, maternally inherited, had been previously report-ed in a boy showing some clinical similarities to this patient [1,15]. Although such chromosomal inversion can occur in healthy individuals [9,15], the author hypothesized the possible occurrence in these two patients of cryptic unbalanced aberrations involving chromosome 2, causally related to the maternally inherited inversion [15]. Indeed, a chromosome 2 interstitial deletion associated with a paternally inherited pericentric inversion (2)(p11.2 q13) has been subsequently reported in a child with dysmorphic features, developmental delay, sensorineural hearing loss, and hypotonia [9].…”
Section: The Main Features Of Baraitser-winter Syndrome Are Reported Inmentioning
confidence: 58%